An Exploration of Subjective-Life of Spirituality and Its Impact - Yusuf Ziya Ogretici (MDPI AG, 2018)
This paper contributes to the discussion on how morality may be uncertain when life orientation changes, for instance, from religious belief to spirituality. Accepting the ‘subjectivation’ thesis as a key concept in understanding the contemporary world, the spiritual realm is treated as a site on which the subjective turn has made a tremendous impact. That turn is investigated particularly in a comparison between “subjective-life„ spirituality and “life-as„ religion. Then, this paper asks what happens to morality when people’s religious belief disappears, changes, or evolves into spiritual experience. Educational practices are also viewed as a resonant field where the subjective turn has impacted on morality. The context of this paper refers to the subjective turn, as explained by The Spiritual Revolution: Why Religion is Giving Way to Spirituality. Then, the comparison of “life-as„ and “subjective-life„ is expressed according to their diverse values. Finally, the conclusion deals with the crucial points of morality in subjective life. In this regard, it is stressed that ‘subjectivation’ is a feature of our time, and presenting a remarkable challenge in the realm of values. Since their orientations are different, ‘subjective-lives’ have a different disposition in morality than the mode of “life-as„. Although it is impossible to generalize concerning whether or not spirituality is moral, nevertheless, it is expected that there will be challenges for religious education when dealing with spirituality.